Optimisation of process parameters to address fundamental challenges during selective laser melting of Ti-6Al-4V: A review - Shipley, H.; McDonnell, D.; Culleton, M.; Coull, R.; Lupoi, R.; O'Donnell, G.; Trimble, D. (International journal of machine tools & manufacture, 2018)
Selective Laser Melting (SLM) is an additive manufacturing (AM) technique which has been heavily investigated for the processing of Ti-6Al-4V (Ti64) which is used in the biomedical, aerospace and other industries. To date the SLM processing of this material has been inhibited by the requirement of post processes due to three primary challenges of martensitic microstructures, undesired porosity and residual stresses which are present in the as-built state. This work identifies the state of the art in process optimisation which is being used to confront these challenges in the as-built state with a view to removing the reliance on post processing. Regarding process optimisation, maximising part density is the primary goal due to the negative influence of pores on fracture and fatigue properties. To accomplish this, a high energy input is required which results in high cooling rates during processing. It is these cooling rates which are instrumental in the microstructural evolution and residual stress production. Accordingly novel methods have been proposed which aim to maintain the necessary high level of energy input but control the cooling rates to tailor the microstructure and reduce residual stresses. Research gaps have been identified pertaining to all three of these challenges when considering mechanical properties of as-built components. Thus in its current state post processes remain critical, however promising techniques in early stage development provide encouragement going forward. •Review of selective laser melting (SLM) of Ti-6Al-4V parts.•Primary challenges: martensitic microstructures, porosity and residual stresses.•Optimisation of processing parameters can address these issues in as-built state.•High cooling rates and energy input are critical factors.